Geomorphology, Sedimentology, Benthic Habitat as Tools for Supporting Coastal Management: Comparison between Australian and Mediterranean Beach Systems - De Muro, S.; Tecchiato, Sira; Buosi, C.; Porta, M.; Bachis, M.; Ibba, A. (2018)
© Coastal Education and Research Foundation, Inc. 2018. The characterization of a nearshore system using geomorphological, sedimentological and ecological data is regarded as baseline knowledge to effectively manage the coast and warrant coastal conservation. Particularly in areas where sediment nourishment is a regular practice, the differentiation between in-situ sediment production and artificial placement, revealed by detailed sediment analyses, is often an important task. In Esperance Bay (Western Australia) sediment nourishment and dumping are ongoing since the 1950s. The comparison with a Mediterranean site (Porto Pino, Sardinia, Italy) has improved the understanding of processes that regulate sediment distribution in the urbanized beach system of Esperance Bay. Porto Pino is a Mediterranean microtidal wave dominated embayment, characterized by environmental conditions similar to those of Esperance (i.e. climate, sediments, geology and benthic habitats), where sediment nourishment was not undertaken previously and the sediment facies can be considered as a natural analogue of the Esperance sediments. The results presented in this paper are useful for Esperance coastal managers as their provide further insights on the distribution of sediment derived from artificial placement.